TECHNOLOGIES AND TOOLS TO IMPROVE THE QUALITY OF UNIVERSITY EDUCATION - Kagosyan, Ashot; Kotovchikhina, Natalia; Poshentseva, Irina; Kashchenko, Tatyana; Aralova, Elena (Revista Inclusiones, 2020)
There are many challenges for education in the modern world. High-quality education today requires understanding the fact that society is becoming more complex. It must constantly adapt to its needs in order to give reliable knowledge to students. The problem of the quality of education and its effective functioning has always been the subject of scientific and practical interest of teachers. Currently, it is acquiring special significance, since ensuring the quality of education is one of the main conditions for trust, mobility, student motivation, and attractiveness of higher education. The purpose of the study is to justify the technologies and tools to improve the quality of university education. The study defines the concept “quality of education” and ways to improve the quality of university education at the theoretical level. Based on the expert survey, a set of measures and processes to improve the quality of education is determined and characterization of the content of the regulations on the organization of the educational process to improve the quality of university education is given.